2013
DOI: 10.1038/ncomms2336
|View full text |Cite
|
Sign up to set email alerts
|

Displays of paternal mouse pup retrieval following communicative interaction with maternal mates

Abstract: Compared with the knowledge of maternal care, much less is known about the factors required for paternal parental care. Here we report that new sires of laboratory mice, though not spontaneously parental, can be induced to show maternal-like parental care (pup retrieval) using signals from dams separated from their pups. During this interaction, the maternal mates emit 38-kHz ultrasonic vocalizations to their male partners, which are equivalent to vocalizations that occur following pheromone stimulation. Witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
115
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 78 publications
(124 citation statements)
references
References 32 publications
9
115
0
Order By: Relevance
“…When mouse sires are continuously housed in the maternal cage with their mates and pups for three to five days prior to and after parturition, they exhibit signs of maternal-like parental care. Furthermore, when separated from their pups for 10 min and co-housed with the dam in a new cage, sires exhibited retrieval behavior when reunited with their pups [14]. We also found that expression of male parental behavior is triggered by olfactory and unique 38-kHz ultrasonic http://dx.doi.org/10.1016/j.neulet.2014.03.078 0304-3940/© 2014 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…When mouse sires are continuously housed in the maternal cage with their mates and pups for three to five days prior to and after parturition, they exhibit signs of maternal-like parental care. Furthermore, when separated from their pups for 10 min and co-housed with the dam in a new cage, sires exhibited retrieval behavior when reunited with their pups [14]. We also found that expression of male parental behavior is triggered by olfactory and unique 38-kHz ultrasonic http://dx.doi.org/10.1016/j.neulet.2014.03.078 0304-3940/© 2014 Elsevier Ireland Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 64%
“…They were then returned to their home cage with five selected pups placed at the opposite side of the nest arena, as illustrated by the schematic in Fig. 1 of Liu et al [14]. As an index of parental behavior, two experts observed the retrieval behavior (the percentage of sires that exhibited retrieval) for 10 min after the reunion of the parent with his/her own pups.…”
Section: Behavioral Testsmentioning
confidence: 99%
See 3 more Smart Citations